Experimental research of bearing with conic pivot with a screw-thread a on it’s surface - Хлопенко, Н.Я.; Кириченко, А.С. (Problems of Tribology, 2014)
Experimental research of thrust bearing with conic pivot with a screw-thread on it’s surface, protected by the patent N 52820 (Ukraine), are performed. It is shown that experience and theory are in good agreement with each other.